THE ROYAL GOVERNESS : A novel of Queen Elizabeth II's Childhood - Holden, Wendy, 1965- (New York : Berkley, 2021)
In 1932, twenty-two-year-old Marion Crawford accepts the role of a lifetime, tutoring their Royal Highnesses Elizabeth and Margaret Rose. Her one stipulation to their parents the Duke and Duchess of York is that she bring some doses of normalcy into the sheltered and privileged lives of the two young princesses. At Buckingham Palace, Windsor Castle, and Balmoral, Marion defies oppressive court protocol to take the girls on tube trains, swimming at public baths, and on joyful Christmas shopping trips at Woolworth's. From her ringside seat at the heart of the British monarchy she witnesses the upheaval of the Abdication and the glamour and drama of the 1937 Coronation. During the war, as Hitler's Heinkels fly over Windsor, she shelters her charges in the castle dungeons (not far from where the Crown Jewels are hidden in a biscuit tin). Afterwards, she is there when Elizabeth first sets eyes on Philip. But being beloved governess and confidante to the Windsor family has come at a cost. She puts her private life on hold until released from royal service following Princess Elizabeth's marriage in 1947. In a majestic story of love, sacrifice, and allegiance, bestselling novelist Holden shines a captivating light into the years before Queen Elizabeth II took the throne, as immortalized on the popular television series The Crown"
Keywords: Elizabeth -- II, -- Queen of Great Britain, -- 1926- -- Fiction; Elizabeth -- II, -- Queen of Great Britain, -- 1926- -- Childhood and youth -- Fiction; Crawford, Marion -- 1909-1988 -- Fiction; Novels; Historical fiction; Biographical fiction; Fiction